2019
DOI: 10.1021/acsomega.9b01342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diamine Addition on Structural Features and Physical Properties of Polyamide 6 Synthesized by Anionic Ring-Opening Polymerization of ε-Caprolactam

Abstract: Synthesis of ε-caprolactam in a twin screw extruder by anionic ring-opening polymerization was successfully carried out to prepare a novel nylon 6 (polyamide 6 (PA6)) containing a small amount of diamine moiety. The produced PA6 shows a remarkable improvement of the physical properties (mechanical properties as well as rheological properties). Added diamine molecules led to some structural changes in the synthesized PA6. The molar ratio of the additive (diamine) to the initiator appeared to be optimum at ca. 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…We tested this approach with the aim of improving the physical properties of the PA6 samples. 9 The variation in the physical properties of the synthesized PA6 samples via single extrusion was similar to that observed for the samples prepared with the diepoxides. 8 17 The mechanical properties of the samples produced with the two methods were similar; thus, we concluded that the reactivity of the diamine additive was similar to that of the diepoxide additive.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…We tested this approach with the aim of improving the physical properties of the PA6 samples. 9 The variation in the physical properties of the synthesized PA6 samples via single extrusion was similar to that observed for the samples prepared with the diepoxides. 8 17 The mechanical properties of the samples produced with the two methods were similar; thus, we concluded that the reactivity of the diamine additive was similar to that of the diepoxide additive.…”
Section: Resultssupporting
confidence: 69%
“…Diamine is expected to participate in the PA6 synthesis process because the amine group of diamine molecules can be attacked by the anions in the chain growing reactions in the extruder. 9 Depending on the amount of diamine added, the PA6 molecules are cross-linked or form branched PA6. We tested this approach with the aim of improving the physical properties of the PA6 samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations